Analisis Fisikokimia dan Organoleptik Enteral Berbasis Bahan Pangan Lokal Ikan Kembung dan Kacang Hijau untuk Ibu Hamil Kekurangan Energi Kronis - Resty Mauliya Rizky; Nelly Zahra Sarifa; Fitriana Mustikaningrum (Jurnal Pangan dan Gizi, 2026)
Enteral formulas based on local food ingredients have the potential to provide an effective nutritional solution for pregnant women with chronic energy deficiency. Ingredients such as mackerel and mung beans leaves supply high-quality protein, omega-3 fatty acids, iron, vitamins, and minerals essential for fetal growth and maternal health. This study aimed to develop and analyze the nutritional, physical, and sensory qualities of a locally sourced enteral formula as an alternative to commercial products. A completely randomized design was applied with two modified formulas (A and B) and a commercial control formula (Peptisol). Analyses included nutrient content, viscosity, osmolality, flow rate, pH, moisture content, color, and sensory evaluation. Results showed that Formulas A and B contained approximately 288 kcal/250 ml, 22–23 g protein, 8.9 g fat, and an energy density of 1.2 kcal/ml, higher than the control. Osmolality values of Formula A (429.50 mOsmol/kg H₂O) and Formula B (471.50 mOsmol/kg H₂O) were within the safe range, with optimal flow rates (5.23–6.18 ml/s), neutral pH (6.95), and moisture content of 68–73%. Sensory evaluation indicated no significant differences in color and texture among formulas, but the control scored higher for aroma, taste, and overall acceptance. The lower acceptance of the local-based formulas was attributed to the fishy odor of mackerel and the beany flavor of moringa leaves. This study concludes that the locally based enteral formula has high nutritional content and meets physical quality standards, but flavor optimization is required to improve consumer acceptance.